CONTEMPORARY ASPECTS OF TYPES OF VACCINES FOR PREVENTION SARS-COV2 INFECTION - Свижак, Виталий; Свижак, Вероника; Пармар, Харш; Сидорчук, Анюта (SWorldJournal, 2021)
Abstracts. This article deals with the brief review of current available vaccines to prevent SARS-CoV2 infection in people of both genders and different ages, mainly adults.